Assessment of WRF-CO2 simulated vertical profiles of CO2 over Delhi region using aircraft and global model data - Srabanti Ballav; Prabir K. Patra; Manish Naja; Sandipan Mukherjee; Toshinobu Machida (Asian Journal of Atmospheric Environment, 2024)
Abstract High-resolution regional model simulation of CO2 may be more beneficial to reduce the uncertainty in estimation of CO2 source and sink via inverse modeling. However, the study of atmospheric CO2 transport with regional models is rare over India. Here, weather research and forecasting chemistry model adjusted for CO2 (WRF-CO2) is used for simulating vertical profile of CO2 and its assessment is performed over Delhi, India (27.4–28.6° N and 77–96° E) by comparing aircraft observations (CONTRAIL) and a global model (ACTM) data. During August and September, the positive vertical gradient (~ 13.4 ppm) within ~ 2.5 km height is observed due to strong CO2 uptake by newly growing vegetation. A similar pattern (~ 4 ppm) is noticed in February due to photosynthesis by newly growing winter crops. The WRF-CO2 does not show such steep increasing slope (capture up to 5%) during August and September but same for February is estimated ~ 1.7 ppm. Generally, CO2 is quite well mixed between ~ 2.5 and ~ 8 km height above ground which is well simulated by the WRF-CO2 model. During stubble burning period of 2010, the highest gradient within 2.5 km height above ground was recorded in October (− 9.3 ppm), followed by November (− 7.6 ppm). The WRF-CO2 and ACTM models partially capture these gradients (October − 3.3 and − 2.7 ppm and November − 3.8 and − 4.3 ppm respectively). A study of the seasonal variability of CO2 indicates seasonal amplitudes decrease with increasing height (amplitude is ~ 21 ppm at the near ground and ~ 6 ppm at 6–8 km altitude bin). Correlation coefficients (CC) between the WRF-CO2 model and observation are noted to be greater than 0.59 for all the altitude bins. In contrast to simulated fossil CO2, the biospheric CO2 is in phase with observed seasonality, having about 80% at the lowest level and gradually declines with height due to mixing processes, reaching around 60% at the highest level. The model simulation reveals that meteorology plays a significant role of the horizontal and vertical gradient of CO2 over the region.